Effect of Contaminant Flow-rate and Applied Voltage on the Current Density and Electric Field of Polymer Tracking Test - F. L. Muhamedin; M. A. M. Piah; N. A. Othman; Nasir Ahmed Algeelani (Institute of Advanced Engineering and Science, 2016)
Electrical failure due to surface discharge on the insulation material will cause material degradation and eventually lead to system failure. The flow of leakage current (LC) on the insulator surface under wet contamination is used to determine the material degradation level. According to IEC 60587 standard, LC exceeding 60 mA for more than two seconds is considered as failure. In this study, the electric field and current density distributions on the linear low-density polyethylene (LLDPE) and natural rubber blend material have been analyzed using finite element method (FEM) analysis. The physical parameters used in FEM simulation were applied with voltage and contaminant flow rate, in accordance to contaminant conductivity. Tracking test condition according to IEC 60587 standard has been applied as proposed by the reference work in simulation using QuickField FEM software. The results show that the electric field and current density would become critical in higher applied voltage and contaminant flow rate. The highest average and highest maximum current density and electric field are found in both applied voltage of 6 kV and contaminant flow rate of 0.90 mlmin-1.